The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/aec.13227
|View full text |Cite
|
Sign up to set email alerts
|

Methods in amphibian biotelemetry: Two decades in review

Abstract: The use of biotelemetry in amphibian behaviour, migration, dispersal and homing research has increased with the miniaturisation and improved reliability of telemetry equipment. Here we synthesise biotelemetry methods and outcomes from the past two decades of published studies (n = 128; 1 January 2000–31 December 2020). We discuss trends in amphibian study duration, transmitter weight and transmitter attachment methods. The most commonly used harness designs for external transmitter attachment and surgical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 88 publications
(141 reference statements)
0
11
0
Order By: Relevance
“…The tracking device was mounted on the toads around the waist using silicon tubing (diameter 2 mm, Figure 1 ). Silicon tubing is a common material to mount tracking devices on amphibians and appears very tolerable by amphibian skin [ 44 ]. In initial attempts prior to this study, we had already successfully tested the material and observed no damage of the toads’ skin or any other health issues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tracking device was mounted on the toads around the waist using silicon tubing (diameter 2 mm, Figure 1 ). Silicon tubing is a common material to mount tracking devices on amphibians and appears very tolerable by amphibian skin [ 44 ]. In initial attempts prior to this study, we had already successfully tested the material and observed no damage of the toads’ skin or any other health issues.…”
Section: Methodsmentioning
confidence: 99%
“…We aimed for a relative unit mass less than 10% of the toad body mass. While lower percentages have been suggested for other animal groups [ 45 ], this is a commonly used value for amphibian tracking [ 44 ]. It allows observation of natural behavior without harming the animals and has been confirmed as suitable for our study species [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Body mass is clearly instrumental in predicting which tracking method is more likely to be used in frugivore studies; globally, 72% of bird species and 55% of mammal species weigh less than 100g (Wilman et al, 2014), which is the minimum body mass for a 5g tag (typical for commercial GPS tags; Altobelli et al, 2022). In our review the median body mass was 83.4g and 192.8g for birds and mammals, respectively, suggesting that larger animals in general have a significantly increased probability of GPS tags being deployed compared to smaller animals, irrelevant of taxa.…”
Section: Focal Taxamentioning
confidence: 99%
“…Attachment techniques, both external and internal, and their design are assessed, as are issues with mortality. Altobelli et al (2022) identify four recommendations for future study: firstly, attachment methods need to align with the behaviour and ecology of the species of interest; secondly, transmitters should be <10% of the animal's mass; thirdly, consideration of behavioural changes when a harness is attached need to be considered; and fourthly reports on the status of all individuals used need to be recorded as part of the study's reporting. With technology becoming more sophisticated and transmitters becoming smaller, there are great advances to be made in this area.…”
Section: Austral Ecology Editorial Volume 47 Issuementioning
confidence: 99%
“…In the second review, Altobelli et al (2022) assess methods used in amphibian telemetry, focussing on 128 studies published between January 2000 and December 2020 worldwide. Frog telemetry dominates globally, with no studies on salamanders identified in Oceania, Africa or South America.…”
mentioning
confidence: 99%